Interdiscursivity of the Literary Text: Universal and Idiosyncratic Features - Izotova, Natalya; Zhykharieva, Olena (Studia Philologica, 2025)
The article explores universal and idiosyncratic features of interdiscursivity, represented in the selected works of Nobel laureate J. M. Coetzee. Interdiscursivity is defined as a cognitive-communicative strategy for the semantic and structural construction of a literary text, aimed at ensuring the interaction with the reader. It is established that in the examined works, interdiscursivity forms a new model of meaning- and text-creation, characterized by its epistemic properties. These properties are differentiated based on the developed prototype model of discourse, which includes the following features: (1) the type of knowledge underlying the formation of discourse; (2) the pragmatic orientation; (3) the features of linguistic-stylistic, plot-compositional, and narrative organization; (4) the tonal system; (5) the communicative goal. Changes in the epistemic traits of discourse signal a discursive "shift," which is accompanied by the emergence of pragma-stylistic effects such as cognitive-emotional tension, cognitive-emotional dissonance, intensification of reader engagement, semantic gaps/distortion, cognitive overload, etc. Keywords: discourse, text, interdiscursivity, prototype, genre, style, communication.